Amerindian names of Colombian palms (Palmae) - Marmolejo, Diana (2008)
A glossary of 1276 Amerindian names or name variants of palms is presented, representing at least 121 species in 64 aboriginal languages of Colombia. The species with documented names in the largest number of languages are Bactris gasipaes, Oenocarpus bataua, Mauritia flexuosa,Euterpe precatoria, andAstrocaryum chambira, which are five of the most used palms in South America. The languages with the largest number of named species are uitoto (48), tikuna (47), muinane (43), siona (34), sikuani (31) and miraña (30). These figures reflect the detailed studies carried out with these ethnic groups, besides the palm diversity of their territories and their knowledge about it. The names are presented in three separate lists –arranged by species, by language, and a global list of names that includes references for each individual record.